Pelaksanaan Kebijakan Reformasi Peradilan Terhadap Pengelolaan Jabatan Hakim Setelah Perubahan Undang Undang Dasar 1945 - Idul Rishan (Fakultas Hukum Universitas Islam Indonesia, 2019)
In most countries undergoing a political transition phase, judicial reform is one of the strategic agendas in amending the constitution. In the amendment to the Indonesian Constitution of 1945, the idea of judicial reform in the management of judges gave birth to two patterns. The first pattern guarantees judicial independency while the second pattern refers to the institutionalisation of the Judicial Commission. Each of these ideas was followed by a number of other legal policies, including the one-roof system. This study is focused on the implementation of judicial reform in the management of the magistracy after the amendment of the 1945 Constitution. It aims to provide a prescription for the implementation of the judicial reform policies. This is a normative juridical research that uses the historical, statutory, and conceptual approaches. The results conclude that the implementation of judicial reform policies are still looking for the definitive form. The significance of this phase in which interests are being pushed and pulled for nearly two decades has caused judicial reform policies tend to deviate and operate without patterns.